PENERAPAN ECOPRINT TOTEBAG TEKNIK POUNDING BAGI SISWA KELAS 6 SD NEGERI 3 SEBATU: Penerapan Teknik Pounding dalam Pembuatan Totebag Ecoprint - Oka Kembarisna, I Made; Sri Prabawati Kusuma, Ni Wayan (UHN IGB Sugriwa Denpasar, 2026)
The ecoprint tote bag making training activity using the pounding technique aims to raise environmental awareness and creativity among sixth grade students at SD Negeri 3 Sebatu through hands-on practice using natural materials. The main issues raised are the students' low understanding of ecoprint techniques and the lack of integration of environmental conservation education into learning, as well as the lack of integration of environmental conservation values into learning in elementary schools. The research method employs a descriptive qualitative approach through the stages of preparation, socialization, demonstration, practice, and evaluation, involving 19 students and 1 accompanying teacher. The pounding technique was chosen because it is simple, environmentally friendly, does not require special tools, and can produce results immediately. The research results showed that students were highly enthusiastic and able to produce ecoprint tote bags with diverse patterns according to their creativity. The evaluation also revealed an increase in students' creativity, with varied and aesthetically valuable works. Students found the activity enjoyable and easy to understand, though technical challenges such as time constraints, pounding skills, and leaf pigment variations were noted. The conclusion of this study is that the application of ecoprinting using the pounding technique has proven effective in enhancing environmental awareness, fine motor skills, and students' appreciation of the potential of the natural environment. Recommendations for further research include extending the training duration, diversifying ecoprinting techniques, and integrating this activity with cultural arts subjects to strengthen a contextual learning approach.